A role for the MEGF6 gene in predisposition to osteoporosis. (7th October 2020) - Teerlink, Craig C.; Jurynec, Michael J.; Hernandez, Rolando; Stevens, Jeff; Hughes, Dana C.; Brunker, Cherie P.; Rowe, Kerry; Grunwald, David J.; Facelli, Julio C.; Cannon‐Albright, Lisa A.
Abstract: Osteoporosis is a common skeletal disorder characterized by deterioration of bone tissue. The set of genetic factors contributing to osteoporosis is not completely specified. High‐risk osteoporosis pedigrees were analyzed to identify genes that may confer susceptibility to disease. Candidate predisposition variants were identified initially by whole exome sequencing of affected‐relative pairs, approximately cousins, from 10 pedigrees. Variants were filtered on the basis of population frequency, concordance between pairs of cousins, affecting a gene associated with osteoporosis, and likelihood to have functionally damaging, pathogenic consequences. Subsequently, variants were tested for segregation in 68 additional relatives of the index carriers. A rare variant in MEGF6 (rs755467862) showed strong evidence of segregation with the disease phenotype. Predicted protein folding indicated the variant (Cys200Tyr) may disrupt structure of an EGF‐like calcium‐binding domain of MEGF6. Functional analyses demonstrated that complete loss of the paralogous genes megf6a and megf6b in zebrafish resulted in significant delay of cartilage and bone formation. Segregation analyses, in silico protein structure modeling, and functional assays support a role for MEGF6 in predisposition to osteoporosis.